2022
DOI: 10.1371/journal.pone.0258435
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality assessment of five common foods sold at different points of sale in Burkina-Faso

Abstract: The aim of the present study was to assess the microbial quality of five ready-to-eat food such as bread, pasta, rice with sauce, beans and milk sold in five localities of Burkina Faso namely, Ouagadougou, Bobo-Dioulasso, Dakola, Cinkansé and Niangoloko. One hundred and one samples were collected and microbial quality were assessed by evaluating the food hygiene indicators such as total aerobic mesophilic flora, total coliforms, thermotolerant coliforms, yeast and mould. Food safety indicators such as Escheric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Sometimes the microbial content in a specific local drink may fall within the acceptable limit, but may still not be appropriate to use as it may contain pathogenic microorganisms and food safety indicators such as coliforms, Escherichia coli, Salmonella spp., Staphylococcus aureus, and Bacillus cereus. [13]. For instance, Minamor and colleagues [14] carried out microbiological analysis of Pito, an alcoholic local drink in Ghana, and their findings showed that the total viable counts of bacteria were within the acceptable limits.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the microbial content in a specific local drink may fall within the acceptable limit, but may still not be appropriate to use as it may contain pathogenic microorganisms and food safety indicators such as coliforms, Escherichia coli, Salmonella spp., Staphylococcus aureus, and Bacillus cereus. [13]. For instance, Minamor and colleagues [14] carried out microbiological analysis of Pito, an alcoholic local drink in Ghana, and their findings showed that the total viable counts of bacteria were within the acceptable limits.…”
Section: Introductionmentioning
confidence: 99%
“…29 (November Suppl. Issue) : 2023 of microbes such as bacteria in snacks can be used as an indicator in determining the quality of a food microbiologically (Compaore et al, 2022). Several pathogenic bacteria found in food are Coliforms, Escherichia coli, and Staphylococcus aureus which can cause foodborne disease (Bintis, 2017).…”
Section: Introductionmentioning
confidence: 99%